PERAN PENDIDIKAN AGAMA KRISTEN DALAM PEMBENTUKAN KARAKTER ANAK USIA DINI - Jeniati David; Seliana Rede; Ayu Ningtyas Salebu'; Merlianti Timbayo; Rini Rini (CV. Adiba Aisha Amira, 2025)
Christian religious education has an important role in shaping the character of early childhood, but its implementation often faces various challenges. This research aims to analyze the role of Christian religious education in forming the character of early childhood and identify the factors that influence its effectiveness. The research method used is descriptive qualitative with a case study approach at several early childhood education institutions in Indonesia. Data was collected through observation, in-depth interviews with educators, and analysis of curriculum documents. The research results show that Christian religious education contributes significantly in forming moral and spiritual values ​​in children, such as honesty, empathy and a sense of responsibility. However, its effectiveness is influenced by the competence of educators, parental involvement, and the availability of supporting resources. In conclusion, to maximize the role of Christian religious education in forming the character of early childhood, it is necessary to increase the competence of educators, collaborate between educational institutions and parents, and provide adequate resources.